POLA PEMUPUKAN DAN ANALISA KANDUNGAN NITRAT PADA SAYUR BROKOLI ( Brassica oleracea cv. brocolli ) DI PERTANIAN DESA MERDEKA KECAMATAN MERDEKA KABUPATEN KARO TAHUN 2012 - Launeta Maruyun Purba; Taufik Ashar; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2013)
Fertilization System and Laboratory Analysis to the Content of Nitrate on Broccoli Vegetable (Brassica oleracea cv. brocolli ) in the Agricultural of Desa Merdeka Kecamatan Merdeka Kabupaten Karo 2012. Broccoli is a popular vegetable that many people like very much. To have a good grow is demanded much more fertilizer. Naturally, a green vegetable contained Nitrate. To supply fertilizer with more and coutinuosly, resulted in the nature content in Broccoli going to rise up. Nitrate comprising Nitrogen (N) and Oxygen (O). In human body, Nitrate transfered into Nitrite and then got reacted with Hemoglobin forming Methenoglonbine may  cause miss oxygen (hypoxsemia). In blood, it cause Nitrosamid or stomach cancer. On babies well known as “blues babies”. The objective of this study is to determine the requirement in applying fertilizer for Broccoli vegetable comprising of frequency in fertilizing, type and dosage of fertilizer, the method applying the fertilizer, space of plant for fertilizer, as well as to know total content of Nitrate on Broccoli vegetable. This study adopted descriptive survey research with spectroguan Nova Go method. In this case is this case is to count the content of Nitrate compared to standard content of nitrate refers to the ADI ( Acceptable Daily Intake )of the European Commission’s Scientific Committee For Food 1995 namely 3,65 mg/kg. The result of study showed that all  sample as Broccoli vegetable fulfilled the requirement an not exceeding 50 mg/litre. Total fertilizer to apply also not exceeding as standard as determined for chemical fertilizer 1.4 ton per hectare and compost 2 ton per hectare. Frequency of fertilizing not exceeding standard. Noted 6 farmers applied fertilizer on  morning and its plant distance far fertilizer less than 10-25 cm. It is concluded the content of Nitrate on Broccoli vegetable is not exceeding threshold and the pattern of  planting by farmers is not different from standard, it is suggested to everybody be carefull to consume the broccoli vegetables in higher sized and in light green color. Keywords: Broccoli, Fertilizer, Nitrogen.